Predicting the localized flux distribution in three phase induction motor between different stator slot size - Ismail, Daut, Prof. Dr.; Dina Maizana, Maiz Ahmad, Dr.; Nor Shafiqin, Shariffuddin; Nasrul Helmei, Halim; Yanawati, Y.; Mohd Asri, Jusoh; Gomesh Nair, Shasidharan; Pungut, Ibrahim; Abdullah, M.; Syatirah, M. N. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/